2019
DOI: 10.2131/fts.6.9
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of DNA damage of glycidol and glycidol fatty acid esters using Fpg-modified comet assay

Abstract: Glycidol fatty acid esters (GEs) are food process contaminants detected in edible oils. It has been thought that glycidol is released from GEs by lipase in vivo, and shows genotoxicity. While DNA damage from glycidol has been reported, there is very little information on the DNA damaging potency of GEs in vivo. Therefore, we estimated DNA damage of glycidol and glycidyl oleate, which is one type of GEs, using the standard comet assay and a formamidopyrimidine glycosylase(Fpg)-modified comet assay. ICR male mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…The glycidol induce ROS by damaging DNA and proteins in the cells as the epoxide group of the glycidol may react with the macromolecules in the cells (Sevim et al, 2021). The epoxide group of the glycidol have the ability to react with the nucleophilic biomolecules such as protein in the cells that may triggers ROS production (Inagaki et al, 2019). ROS level of treated 116 cells with R-and S-glycidol (Figure 2) had shown that both chemicals are able to induce oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…The glycidol induce ROS by damaging DNA and proteins in the cells as the epoxide group of the glycidol may react with the macromolecules in the cells (Sevim et al, 2021). The epoxide group of the glycidol have the ability to react with the nucleophilic biomolecules such as protein in the cells that may triggers ROS production (Inagaki et al, 2019). ROS level of treated 116 cells with R-and S-glycidol (Figure 2) had shown that both chemicals are able to induce oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Micronucleus induction has been confirmed in the bone marrow cells of ICR mice exposed to glycidol using micronucleus test [ 4 ]. Oxidative DNA damaging potency of glycidol in the comet assay was reported using Fpg-modified comet assay [ 5 ]. Therefore, diHOPrVal, the Hb adduct of glycidol, has been used as a biomarker that can assess exposure to GEs and glycidol [ 10 , 11 , 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…GEs, which have fatty acid in their structure, are degraded by lipase, a lipolytic enzyme, consequently producing glycidol (2,3-epoxy-1-propanol) when ingested by the body through the diet ( Figure 1 ) [ 2 ]. Glycidol is known as a genotoxic epoxide compound and has been reported to induce carcinogenicity [ 3 , 4 , 5 ], chromosomal aberration induction, neurotoxicity, and mutagenicity [ 6 , 7 , 8 , 9 ]. In view of the genotoxic and carcinogenic potential of glycidol, it is important to assess the exposure of GEs to humans from the food and environment for public health perspective.…”
Section: Introductionmentioning
confidence: 99%
“…Glycidyl esters (GE or GEs) are thermal processing hazards that are mainly formed from diacylglycerol during deodorization of refined vegetable oils due to high temperature (>200 °C). , When ingested with edible oil, GEs can be rapidly digested by the gastrointestinal tract to form glycidol, which has been classified as a “group 2A” carcinogen (probably carcinogenic to humans) by the International Agency for Research on Cancer (IARC) . Recently, GEs have also been confirmed that they present a significant genetic damage in the kidney, liver, and blood of mice . It has been well known that GEs are widely found in refined vegetable oils, particularly in palm oil and rice oil, and even also detected in infant formula and baby food products containing refined vegetable oils. , Consequently, more and more researchers have been focusing on studying the formation and inhibition of GEs in refined vegetable oils in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…4 Recently, GEs have also been confirmed that they present a significant genetic damage in the kidney, liver, and blood of mice. 5 It has been well known that GEs are widely found in refined vegetable oils, particularly in palm oil and rice oil, 6 and even also detected in infant formula and baby food products containing refined vegetable oils. 7,8 Consequently, more and more researchers have been focusing on studying the formation and inhibition of GEs in refined vegetable oils in recent years.…”
Section: ■ Introductionmentioning
confidence: 99%